Effects of Different Ligands in the Notch Signaling Pathway on the Proliferation and Transdifferentiation of Primary Type II Alveolar Epithelial Cells - Liu, Xiuxiang; Zhu, Xiaoxi; Zhu, Guoqing; Wang, Chaoyun; Gao, Ruiwei; Ma, Jinshuai (Frontiers in Pediatrics, 2020)
Background: Transdifferentiation of type II alveolar epithelial cells (AECII) into type I alveolar epithelial cells (AECI) is involved in neonatal respiratory distress syndrome (NRDS). Different ligands of the Notch pathway could have different effects on AECII transdifferentiation. Objective: To investigate the effects of Dlk1 and Jagged1 on the proliferation and transdifferentiation of AECII. Methods: Fetal AECIIs (19 days of gestation) were divided: control group, Dlk1 group, rhNF-κB group. Proliferation was tested using the MTT assay. Expression of surfactant protein C (SP-C) and aquaporin 5 (AQP5) was examined by immunofluorescence. mRNA and protein levels of SP-C, AQP5, Nortch1, Dlk1, Jagged1, and Hes1 were examined by RT-PCR and western blot. Results: In response to Dlk1, cell number and proliferation were increased (P<0.05), and mRNA and protein levels of SP-C, Dlk1, Notch1 and Hes1 were up-regulated,while AQP and Jagged1 were decreased. In response to rhNF-κB, the cell number and proliferation were reduced, and mRNA and protein levels of Jagged1 and Notch1 were up-regulated, while Dlk1 and SP-C were downregulated. In the Dlk1 group, SP-C and AQP5 expression patterns suggested that the cells were still